2014
DOI: 10.1021/la500221n
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of a Nonpolar Liquid with an Alcohol

Abstract: Nonpolar liquids whose dielectric permittivities are close to 2 have very low conductivities, usually below 10 × 10(-10) S/m. Their ionization is suppressed by the lack of solvation resulting from the negligible dipole moment of such liquids' molecules. Ionization could be enhanced by the addition of other substances that could serve as solvating agents, creating inverse micelles around ions and preventing them from reassociating into ion pairs and neutral molecules. Surfactants are normally used for this purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 21 publications
(28 reference statements)
6
29
0
Order By: Relevance
“…The conductivity increases sharply with the mass concentration of alcohol. This sharp increase was …rst shown by Dukhin et al in a recent series of articles [9][10] [11]. <Fig 1.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The conductivity increases sharply with the mass concentration of alcohol. This sharp increase was …rst shown by Dukhin et al in a recent series of articles [9][10] [11]. <Fig 1.…”
Section: Resultsmentioning
confidence: 59%
“…Twenty years later, they adequately gave the results as a linear plot of the logarithm of the equilibrium constant as a function of the inverse of the permittivity [4]. Recently, there has been a growing interest for the conductivity of surfactants in non-polar medium [6] [7] [8] and for the conductivity of mixtures of pure solvents [9][10] [11]. In some cases, the chemical potential of the ionogenic species is not a¤ected by the creation of ions or of ion-pairs.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, experimental work has been published on mixture of alcohol and hydrocarbons by Dukhin and co-workers. 10,11 On these mixtures, only one other publication can be found, on the conductivity of mixtures of ethanol and gasoline. 32 In the first article, 10 written by Dukhin and Bombard, the conductivity of a mixture of n-octanol and an alcane (PAO) of similar viscosity was measured.…”
Section: Discussion About Recent Experimental Findingsmentioning
confidence: 99%
“…10,11 On these mixtures, only one other publication can be found, on the conductivity of mixtures of ethanol and gasoline. 32 In the first article, 10 written by Dukhin and Bombard, the conductivity of a mixture of n-octanol and an alcane (PAO) of similar viscosity was measured. The authors found a very non-linear dependence (almost an exponential dependence) of the conductivity on the fraction of alcohol.…”
Section: Discussion About Recent Experimental Findingsmentioning
confidence: 99%
“…A recent study by Bombard and Dukhin [32] showed that the electrical conductivity of poly(α-olefin) (PAO)/1-octanol mixtures increased by five orders of magnitude between 100% PAO and 100% octanol. This prompted the authors to propose an ionization mechanism, involving alcohol autoprotolysis above a "critical micelle concentration" (≈20 wt% octanol), as being responsible.…”
Section: Electrical Conduction In Non-aqueous Liquidsmentioning
confidence: 99%